ANALISIS PERPUTARAN KAS TERHADAP PROFITABILITAS (ROA) PADA PT. KIMIA FARMA, TBK. PERIODE 2013-2017 - Rachmawati (PARAMETER, 2020)
This research aims to determine the effect of cash turnover on profitability (ROA) at PT. Kimia Farma, Tbk period 2013-2017.. This research is a research of two variables that using qualitative descriptive methods. The independent variable is cash turnover and the dependent variable is profitability. The analysis technique used is simple linear regression analysis, correlation analysis, coefficient of determination analysis, and t test. The results of the research analysis show that cash turnover has a relation on profitability. The results of the research can be seen in the correlation analysis (r) with the correlation obtained is equal to 0,65 which means that cash turnover has a strong relation on profitability. The results of the determination coefficient analysis is equal to 42,25% profitability is influenced by cash turnover while 57,75% is influenced by other factors or variables that not included in this research. And the result of the t test are Tcount < Ttable (1,48 < 3,182) then Ho is accepted and Ha is rejected because the results are not significant.